Post-COVID-19 acute sarcopenia: physiopathology and management - Piotrowicz, Karolina; Gąsowski, Jerzy; Michel, Jean-Pierre; Veronese, Nicola (Aging clinical and experimental research, 2021)
In this review, we discuss the pathophysiologic and management aspects of acute sarcopenia in relation to SARS-CoV-2 infection. COVID-19 is as a multi-organ infectious disease characterized by a severe inflammatory and highly catabolic status, influencing the deep changes in the body build, especially the amount, structure, and function of skeletal muscles which would amount to acutely developed sarcopenia. Acute sarcopenia may largely impact patients’ in-hospital prognosis as well as the vulnerability to the post-COVID-19 functional and physical deterioration. The individual outcome of the COVID-19 and the degree of muscle mass and functional loss may be influenced by multiple factors, including the patient’s general pre-infection medical and functional condition, especially in older adults. This paper gathers the information about how the SARS-CoV-2 hyper-inflammatory involvement exacerbates the immunosenescence process, enhances the endothelial damage, and due to mitochondrial dysfunction and autophagy, induces myofibrillar breakdown and muscle degradation. The aftermath of these acute and complex immunological SARS-CoV-2-related phenomena, augmented by anosmia, ageusia and altered microbiota may lead to decreased food intake and exacerbated catabolism. Moreover, the imposed physical inactivity, lock-down, quarantine or acute hospitalization with bedrest would intensify the acute sarcopenia process. All these deleterious mechanisms must be swiftly put to a check by a multidisciplinary approach including nutritional support, early physical as well cardio-pulmonary rehabilitation, and psychological support and cognitive training. The proposed holistic and early management of COVID-19 patients appears essential to minimize the disastrous functional outcomes of this disease and allow avoiding the long COVID-19 syndrome.